Developing Customer Satisfaction Measurement Model Based on ‘CHARACTER’ Dimension in Polman Bandung - Emma Dwi Ariyani; Supriyadi Sadikin; Achmad Muhammad (Soshum: Jurnal Sosial dan Humaniora, 2023)
Considering Polman Bandung is a public higher education institution, it has a responsibility to evaluate how satisfactorily its services are received by its customers. However, Polman Bandung currently lacks a valid and reliable measurement tool, so it is necessary to create one so that the results can be more credibly reported. This study aims to obtain an instrument model for measuring customer satisfaction with the services provided by Polman Bandung. This study was a qualitative analysis study using the grounded research methodology to obtain new perspectives for developing customer satisfaction measuring tools.  Activities that have been carried out include formulating the dimensions of customer satisfaction to be measured by combining 14 elements of the community service satisfaction index from KEMENPAN no.25/2004, 9 elements of service satisfaction dimensions from PERMENPAN no.14/2017, and the CARTER dimension which consists of 6 dimensions so that new dimensions are obtained in measuring service satisfaction with Polman Bandung institutions. The dimensions formulated into CHARACTER consist of 9 dimensions, namely Compliance, Handling complaints, Assurance, Reliability, Ability to serve, Clarity, Tangibility, Empathy, and Responsiveness. These nine dimensions are then derived into question items in the form of a questionnaire used to measure the level of service satisfaction provided by the institution to its customers. Responses from 757 respondents from internal and external customers were used in the quantitative analysis to test the validity and reliability of the measurement instrument. The result of this research showed measurement instrument's validity and reliability tests revealed that 18 elements are determined to be valid, and the highest validity value for each dimension is chosen to serve as a question item in the instrument that has up to 9 question items, in addition, the Cronbach's alpha reliability number is 0.945, allowing for proper use of the tool.